The Influence of Investment Decisions, Funding, and Profitability on Company Value with Corporate Governance as Moderator - Danny Adhitya; Suwardi Bambang Hermanto; Lilis Ardini (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
This study aims to examine and analyze the effect of investment decisions, funding decisions, and profitability on firm value with corporate governance as the moderating variable. With the existence of corporate governance as a moderating variable, it is expected to make company managers to choose and decide on investment decisions, funding decisions and profitability correctly. This research was conducted on companies that went public on the Indonesia Stock Exchange in the period 2014 to 2018. The study tested samples using the purposive sampling method on 10 companies in the infrastructure, utilities and transportation sectors from 50 financial statements that were observed. The independent variables consist of market book value, debt to equity ratio, and return on assets, while the dependent variable is price book value, and the moderating variable is managerial ownership. Test analysis using multiple linear regression using Statistical Product and Service Solutions (SPSS) software. The results of the analysis show that the investment decision variables and funding decisions have a positive effect on firm value. While the profitability variable has no effect on firm value, and the corporate governance variable does not moderate the influence between investment decisions, funding decisions, and profitability on firm value.